A heterobimetallic tetrahedron from a linear platinum(II)-bis(acetylide) metalloligand - Hardy, Matthias; Engeser, Marianne; Lützen, Arne (Beilstein Journal of Organic Chemistry, 2020)
Employing 4-ethynylaniline as a simple organic ligand we were able to prepare the stable trans-bis(acetylide)platinum(II) complex [Pt(L1)2(PBu3)2] as a linear metalloligand. The reaction of this metalloligand with iron(II) cations and pyridine-2-carbaldehyde according to the subcomponent self-assembly approach yielded decanuclear heterobimetallic tetrahedron [Fe4Pt6(L2)12](OTf)8. Thus, combination of these two design concepts – the subcomponent self-assembly strategy and the complex-as-a-ligand approach – ensured a fast and easy synthesis of large heterobimetallic coordination cages of tetrahedral shape with a diameter of more than 3 nm as a mixture of all three possible T-, S4- and C3-symmetric diastereomers. The new complexes were characterized by NMR and UV–vis spectroscopy and ESI mass spectrometry. Using GFN2-xTB we generated energy-minimized models of the diastereomers of this cage that further corroborated the results from analytical findings.
Keywords: cage compounds; heterobimetallic complexes; pyridylimine ligands; self-assembly; supramolecular chemistry

(untitled) - Smulders, M. M. J.; Riddell, I. A.; Browne, C.; Nitschke, J. R. (Chem. Soc. Rev., 2013)

(untitled) - Harris, K.; Fujita, D.; Fujita, M. (Chem. Commun., 2013)

(untitled) - Chen, L.; Chen, Q.; Wu, M.; Jiang, F.; Hong, M. (Acc. Chem. Res., 2015)

(untitled) - Brown, C. J.; Toste, F. D.; Bergman, R. G.; Raymond, K. N. (Chem. Rev., 2015)

(untitled) - Cook, T. R.; Stang, P. J. (Chem. Rev., 2015)

(untitled) - Park, J.; Chen, Y.-P.; Perry, Z.; Li, J.-R.; Zhou, H.-C. (J. Am. Chem. Soc., 2014)

(untitled) - Käseborn, M.; Holstein, J. J.; Clever, G. H.; Lützen, A. (Angew. Chem., Int. Ed., 2018)
Angew. Chem. 2018, 130, 12349–12353. doi:10.1002/ange.201806814

(untitled) - Beves, J. E.; Blight, B. A.; Campbell, C. J.; Leigh, D. A.; McBurney, R. T. (Angew. Chem., Int. Ed., 2011)
Angew. Chem. 2011, 123, 9428–9499. doi:10.1002/ange.201007963

(untitled) - Schulte, T. R.; Holstein, J. J.; Clever, G. H. (Angew. Chem., Int. Ed., 2019)
Angew. Chem. 2019, 131, 5618–5622. doi:10.1002/ange.201812926

(untitled) - Zhu, R.; Regeni, I.; Holstein, J. J.; Dittrich, B.; Simon, M.; Prévost, S.; Gradzielski, M.; Clever, G. H. (Angew. Chem., Int. Ed., 2018)
Angew. Chem. 2018, 130, 13840–13844. doi:10.1002/ange.201806047

(untitled) - Kumar, A.; Mukherjee, P. S. (Chem. – Eur. J., 2020)

(untitled) - Siddiqui, M. M.; Saha, R.; Mukherjee, P. S. (Inorg. Chem., 2019)

(untitled) - Fujita, D.; Ueda, Y.; Sato, S.; Yokoyama, H.; Mizuno, N.; Kumasaka, T.; Fujita, M. (Chem, 2016)

(untitled) - Bhat, I. A.; Samanta, D.; Mukherjee, P. S. (J. Am. Chem. Soc., 2015)

(untitled) - Saha, M. L.; Neogi, S.; Schmittel, M. (Dalton Trans., 2014)

(untitled) - Han, M.; Engelhard, D. M.; Clever, G. H. (Chem. Soc. Rev., 2014)

(untitled) - Lu, Z.; Ronson, T. K.; Nitschke, J. R. (Chem. Sci., 2020)

(untitled) - Castilla, A. M.; Ramsay, W. J.; Nitschke, J. R. (Acc. Chem. Res., 2014)

(untitled) - Nitschke, J. R. (Acc. Chem. Res., 2007)

(untitled) - Frischmann, P. D.; Kunz, V.; Stepanenko, V.; Würthner, F. (Chem. – Eur. J., 2015)

(untitled) - Saha, R.; Samanta, D.; Bhattacharyya, A. J.; Mukherjee, P. S. (Chem. – Eur. J., 2017)

(untitled) - Rizzuto, F. J.; Nitschke, J. R. (J. Am. Chem. Soc., 2020)

(untitled) - Nguyen, B.-N. T.; Grommet, A. B.; Tron, A.; Georges, M. C. A.; Nitschke, J. R. (Adv. Mater. (Weinheim, Ger.), 2020)

(untitled) - Yang, Q.; Tang, J. (Dalton Trans., 2019)

(untitled) - Zhang, Y.-Y.; Gao, W.-X.; Lin, L.; Jin, G.-X. (Coord. Chem. Rev., 2017)

(untitled) - Li, H.; Yao, Z.-J.; Liu, D.; Jin, G.-X. (Coord. Chem. Rev., 2015)

(untitled) - Hahn, F. E.; Offermann, M.; Schulze Isfort, C.; Pape, T.; Fröhlich, R. (Angew. Chem., 2008)
Angew. Chem., Int. Ed. 2008, 47, 6794-6797. doi:10.1002/anie.200801172

(untitled) - Kreickmann, T.; Hahn, F. E. (Chem. Commun., 2007)

(untitled) - Hardy, M.; Struch, N.; Topić, F.; Schnakenburg, G.; Rissanen, K.; Lützen, A. (Inorg. Chem., 2018)

(untitled) - Reichel, F.; Clegg, J. K.; Gloe, K.; Gloe, K.; Weigand, J. J.; Reynolds, J. K.; Li, C.-G.; Aldrich-Wright, J. R.; Kepert, C. J.; Lindoy, L. F.; Yao, H.-C.; Li, F. (Inorg. Chem., 2014)

(untitled) - Hardy, M.; Struch, N.; Holstein, J. J.; Schnakenburg, G.; Wagner, N.; Beck, J.; Engeser, M.; Clever, G. H.; Lützen, A. (Angew. Chem., 2020)
Angew. Chem., Int. Ed. 2020, 59, 3195–3200. doi:10.1002/anie.201914629

(untitled) - Hiraoka, S.; Sakata, Y.; Shionoya, M. (J. Am. Chem. Soc., 2008)

(untitled) - Maity, M.; Howlader, P.; Mukherjee, P. S. (Cryst. Growth Des., 2018)

(untitled) - Fan, Q.-J.; Lin, Y.-J.; Hahn, F. E.; Jin, G.-X. (Dalton Trans., 2018)

(untitled) - Zhang, W.-Y.; Lin, Y.-J.; Han, Y.-F.; Jin, G.-X. (J. Am. Chem. Soc., 2016)

(untitled) - Vajpayee, V.; Kim, H.; Mishra, A.; Mukherjee, P. S.; Stang, P. J.; Lee, M. H.; Kim, H. K.; Chi, K.-W. (Dalton Trans., 2011)

(untitled) - Adeyemo, A. A.; Mukherjee, P. S. (Beilstein J. Org. Chem., 2018)

(untitled) - Metherell, A. J.; Ward, M. D. (Chem. Commun., 2014)

(untitled) - Ryu, J. Y.; Park, Y. J.; Park, H.-R.; Saha, M. L.; Stang, P. J.; Lee, J. (J. Am. Chem. Soc., 2015)

(untitled) - Hardy, M.; Lützen, A. (Chem. – Eur. J., 2020)

(untitled) - Jansze, S. M.; Cecot, G.; Wise, M. D.; Zhurov, K. O.; Ronson, T. K.; Castilla, A. M.; Finelli, A.; Pattison, P.; Solari, E.; Scopelliti, R.; Zelinskii, G. E.; Vologzhanina, A. V.; et al. (J. Am. Chem. Soc., 2016)

(untitled) - Zhang, Y.; Crawley, M. R.; Hauke, C. E.; Friedman, A. E.; Cook, T. R. (Inorg. Chem., 2017)

(untitled) - Wang, W.; Wang, Y.-X.; Yang, H.-B. (Chem. Soc. Rev., 2016)

(untitled) - Bhat, I. A.; Zangrando, E.; Mukherjee, P. S. (Inorg. Chem., 2019)

(untitled) - Smulders, M. M. J.; Jiménez, A.; Nitschke, J. R. (Angew. Chem., Int. Ed., 2012)
Angew. Chem. 2012, 124, 6785–6789. doi:10.1002/ange.201202050

(untitled) - Masai, H.; Liu, M.; Tachibana, Y.; Tsuda, S.; Terao, J. (J. Org. Chem., 2020)

(untitled) - Cooper, T. M.; Haley, J. E.; Krein, D. M.; Burke, A. R.; Slagle, J. E.; Mikhailov, A.; Rebane, A. (J. Phys. Chem. A, 2017)

(untitled) - Wang, X.; Han, Y.; Liu, Y.; Zou, G.; Gao, Z.; Wang, F. (Angew. Chem., Int. Ed., 2017)
Angew. Chem. 2017, 129, 12640–12644. doi:10.1002/ange.201704294

(untitled) - Lee, S. J.; Luman, C. R.; Castellano, F. N.; Lin, W. (Chem. Commun., 2003)

(untitled) - Goeb, S.; Prusakova, V.; Wang, X.; Vézinat, A.; Sallé, M.; Castellano, F. N. (Chem. Commun., 2011)

(untitled) - Zhang, M.; Xu, H.; Wang, M.; Saha, M. L.; Zhou, Z.; Yan, X.; Wang, H.; Li, X.; Huang, F.; She, N.; Stang, P. J. (Inorg. Chem., 2017)

(untitled) - Zhang, J.; Zhang, J.; Hao, G.; Xin, W.; Yang, F.; Zhu, M.; Zhou, H. (J. Med. Chem., 2019)

(untitled) - Deeming, A. J.; Hogarth, G.; Lee, M.-y. (Venus).; Saha, M.; Redmond, S. P.; Phetmung, H. (Taya).; Orpen, A. G. (Inorg. Chim. Acta, 2000)

(untitled) - Gütlich, P.; Hauser, A.; Spiering, H. (Angew. Chem., Int. Ed. Engl., 1994)

(untitled) - Grimme, S.; Bannwarth, C.; Shushkov, P. (J. Chem. Theory Comput., 2017)

(untitled) - Bannwarth, C.; Ehlert, S.; Grimme, S. (J. Chem. Theory Comput., 2019)

(untitled) - Yang, W.; Karatay, A.; Zhao, J.; Song, J.; Zhao, L.; Xing, Y.; Zhang, C.; He, C.; Yaglioglu, H. G.; Hayvali, M.; Elmali, A.; Küçüköz, B. (Inorg. Chem., 2015)